Content Based Medical Image Retrieval-A Survey - Manjula Gururaj Rao, H; Nagaraja, GS (International Journal of Computer Sciences and Engineering, 2025)
In today’s world medical images play a vital role. Retrieving the correct information from medical images is the very difficult and time consuming. This paper presents the overview of content based image retrieval processing such as how medical images are processed and what are the techniques used for processing. This paper also discusses the difficulties in processing of the medical images and how to overcome difficulties. This paper overall gives an innovative idea of how content based image retrieval is employed in the medical images.